The Precision Agriculture Revolution in the United States: The Utilization of Drone Technology and Big Data - Judijanto, Loso; Zaki, Amin; Razak, Faisal (Techno Agriculturae Studium of Research, 2024)
Precision agriculture is an innovative approach that is increasingly being applied in the United States to increase agricultural productivity through the use of cutting-edge technology. The background of this research focuses on the importance of adopting modern technologies, such as drones and big data, in addressing global challenges such as climate change, resource limitations, and increasing food needs. The purpose of this study is to explore how the integration of drone technology and big data can revolutionize the agricultural sector in the United States, specifically in improving efficiency, reducing waste, and increasing crop yields. This study uses a qualitative method with a case study approach to several agricultural companies that have adopted drone technology and big data. Data collection was carried out through in-depth interviews with farmers, document analysis, and field observations regarding the implementation of the technology. The data collected was then analyzed using thematic analysis methods to identify patterns and impacts that arise from the adoption of this technology. The results show that the use of drones allows for real-time monitoring of land, early detection of plant diseases, and more efficient resource management, while big data helps in more accurate data-driven decision-making. These two technologies significantly improve the productivity and sustainability of agriculture in the study area. The conclusion of this study confirms that the integration of drone technology and big data can make a great contribution in facing the challenges of modern agriculture. Precision agriculture, with the support of technology, has the potential to be a long-term solution to improve the efficiency and yield of agricultural production.